2019
DOI: 10.1101/643643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of key regulators in Prostate cancer from gene expression datasets of patients

Abstract: Identification of key regulators and regulatory pathways is an important step in the discovery of genes involved in cancer. Here, we propose a method to identify key regulators in prostate cancer (PCa) from a network constructed from gene expression datasets of PCa patients.Overexpressed genes were identified using BioXpress, having a mutational status according to COSMIC, followed by the construction of PCa Interactome network using the curated genes.The topological parameters of the network exhibited power l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
(107 reference statements)
1
3
0
Order By: Relevance
“…This implies that triangular motifs is correlated with signalling network of cancer. Indeed, triangular network motifs are abundantly found in many cancer studies using network biology approach [54][55][56][57][58][59][60]. Our study thus highlights a close relation between thermodynamic cost-precision (thermodynamic uncertainty relation), triangular motifs and cancer.…”
Section: Discussionsupporting
confidence: 61%
“…This implies that triangular motifs is correlated with signalling network of cancer. Indeed, triangular network motifs are abundantly found in many cancer studies using network biology approach [54][55][56][57][58][59][60]. Our study thus highlights a close relation between thermodynamic cost-precision (thermodynamic uncertainty relation), triangular motifs and cancer.…”
Section: Discussionsupporting
confidence: 61%
“…The PPI study of the identified protein sets and the protein community finding by in silico network analysis identified a set of key regulator molecules [42][43][44][45] Upon TXR treatment, the C9, AAG and catalase abundance were decreased almost to the basal levels without significant alteration in CRP, a non-specific indicator of inflammation. High aldehyde dehydrogenase (ALDH) activity has been reported in osteoarthritis patients'…”
Section: Discussionmentioning
confidence: 99%
“…These experiments involve eliminating the most in uential nodes in the network and studying the resulting reorganized networks. [36,37]. Furthermore, in uential nodes have been identi ed using community detection-based methods [38,39].…”
Section: Related Workmentioning
confidence: 99%